Performance analysis of different geotextile materials in extensive roof garden designs - Akat Saracoglu, Ozlem; Cakar, Handan; Akat, Hulya; Adanacioglu, Hakan (Journal of Environmental Engineering and Landscape Management, 2022)
Roof garden arrangements, which have emerged in recent years based on environmentally friendly approaches, not only increase urban aesthetics but are also a design approach that contributes to the solution of problems caused by climate change. In this study, the filtration performance of different geotextile materials was investigated based on the extensive roof garden model. The studies related to the research were carried out as an open field pot experiment in Ege University Bayindir Vocational School. Crassula ovata from succulent group plants was used as plant material. 3 filtration materials were tested as filter layers, namely glass fibre, raw cotton, and polypropylene fabric. Various statistical analyses were applied to determine the effectiveness of the filtration materials in extensive roof garden applications. According to statistical significance levels it can be said that the use of polypropylene fabric as filtration material would be more advantageous compared to alternative geotextile materials.